Ontologies and linguistics: a relationship that strengthens knowledge representation (Advances in Knowledge Representation, 2021)
The ontologies theme has already established itself as a research theme in Information Science, as a Knowledge Organization System. However, this theme arouses the interest of several other areas – Computer Science, Philosophy, Medicine, Literature, and others – establishing itself as a comprehensive theme that is enhanced by interdisciplinary research. In this first interview in the Fronteira Journal of Knowledge Representation, we invite Professor Heliana Mello to contribute to the interdisciplinary vision of research on ontologies and knowledge representation in the field of linguistics.